Manajemen Sumber Daya Manusia Islam: Sejarah, Nilai, dan Benturan - Ihsan Rahmat; Netta Agusti (JURNAL ILMIAH SYI'AR, 2018)
Human resource management (HRM) in Western perspectives continue to be questioned in the East, especially from Islamic academics. There is hope to implement religious teachings in the organizational sphere. Generally, this paper discusses issues in Islamic HRM, questioning the extent to which Islam (text and context) governs people in organizations. Putting forward the literature sourced from the pages of Ebsco and Emerald using the keywords "Islamic Human Resources Management." Found 96 journals, but only 21 contained the themes we meant. Then read intensively, make mapping, determine the main ideas of each journal, and group ideas based on themes. These themes were discussed: the internalization of Islam in HRM, Islamic values in HRM, developments in Muslim countries, and the challenges of Islamic HRM. This paper found religion entered the organizational realm not far after the discussion of industrial psychology was discussed. Using framework of 'the management theory jungle', the role of religion in organizations can be explained. HRM is a Western product that emerged after the industrial revolution. The argument positions Islam as a regulator of halal-haram restrictions on human activities in the organization. Furthermore, the cultural phenomenon above religion is also a hot issue. Managers know, understand, and acknowledge the goodness of Islam, but not yet for practice. So far, the expert study of Islamic HRM is still merely exploring values based on four sources, namely the Qur'an, Hadith, Ijma ', and Qiyash. Need best practice research, so that later it will be able to bring up the Islamic HRM curriculum.